Converging longitudinal patterns of atrophy in clinical variants of frontotemporal lobar degeneration. (1st February 2022) - Spinelli, Edoardo Gioele; Basaia, Silvia; Cividini, Camilla; Riva, Nilo; Magnani, Giuseppe; Caso, Francesca; Caroppo, Paola; Prioni, Sara; Tremolizzo, Lucio; Appollonio, Ildebrando; Silani, Vincenzo; Carrera, Paola; et al.
Abstract: Background: The aim of this study was to assess longitudinal patterns of atrophy shown by magnetic resonance imaging (MRI) in the whole‐brain GM of patients affected by different clinical variants of the FTLD spectrum. Method: Fifty‐nine patients, including 26 with behavioral variant of frontotemporal dementia (bvFTD), 10 non‐fluent/agrammatic variant of primary progressive aphasia (nfvPPA), 12 semantic variant of PPA (svPPA), and 11 MND, in the absence of known pathogenic mutations, underwent MRI on a 3T scanner at 6‐month intervals for one year. Thirty‐three healthy controls underwent the same protocol. 3D T1‐weighted MRI sequences were analyzed using voxel‐based morphometry to assess the longitudinal evolution of GM atrophy in patients, compared with HC. Result: At baseline, severe diffuse atrophy of frontotemporal cortical regions and basal ganglia was found in bvFTD, nfvPPA and svPPA groups, whereas MND did not show significant GM atrophy. At 6‐month follow‐up, bvFTD and PPA groups showed significant progression of atrophy in the insular (bvFTD, nfvPPA and svPPA) and anterior cingulate cortex (bvFTD and nfvPPA), bilaterally, as well as in the left caudate nucleus and middle temporal cortex (svPPA). At 12‐month follow‐up, similar patterns of atrophy progression were found, with the additional involvement of the superior frontal cortical gyri in nfvPPA, bilaterally, and the right hippocampus in svPPA. No significant progression of atrophy was found in MND patients. Conclusion: Our data suggest that atrophy of insular and anterior cingulate cortical regions closely reflects the progression of neurodegeneration across the behavioral and linguistic presentations of frontotemporal dementia (FTD), in contrast with a substantial sparing of GM in MND. Supported by: European Research Council (StG‐2016_714388_NeuroTRACK).